Mexican Migrants to the United States: an Alternative Methodology - Martínez, José (Universidad Autónoma de Nuevo León, 2013)
Mexicans are the largest immigrant group in the United States. There is a lack of consensus about whether migrants from Mexico are positively or negatively selected. Data from the Mexican census suggest migrants are negatively selected while data from the U.S. census suggest intermediate selection. Both data sources undercount migrants, with Mexican sources systematically undercounting more educated migrants and U.S. sources undercounting less educated migrants. Net migration techniques are used to estimate migration flows during the 1990s and obtain estimates which present a more accurate characterization of Mexican immigrants. Three main conclusions are reached. First, the net flow of Mexicans to the United States during the 1990s was about 10 percent less than the U.S. census data suggest. Second, migrants are younger and less female than suggested by the U.S. census, but older and more female than suggested by the Mexican census. Third, U.S. census data significantly overstate the educational attainment of migrants. However, the disagreement in the literature on migrant selection results less from who is counted in Mexican and U.S. data and more on the responses given to the Mexican and U.S. census questions on schooling. JEL Classification: F22, O15, J15.